Lithium manganate positive electrode material and preparation method and application thereof

Through dry mixing and segmented reverse sequence sintering technology, the problem of poor capacity attenuation and circulation performance of lithium manganese oxide positive electrode material at high temperature is solved, and a material with low internal resistance and high capacity is prepared, which is suitable for industrial production, and is realized Lithium-ion batteries have improved performance.

CN119176582APending Publication Date: 2024-12-24TAIZHOU SHANNENG TECH CO LTD

Patent Information

Application Number
CN202411326458.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

The existing lithium manganate positive electrode materials have fast reversible capacity attenuation at high temperatures, poor circulation performance, and complex preparation process and high cost, making it difficult to be suitable for industrial production.

Method used

Dry ball milling and secondary ball milling are carried out by mixing manganese sources, lithium sources and additives (such as niobium pentoxide, aluminum fluoride, aluminum hydroxide, lithium fluoride, etc.) , combined with segmented reverse sequence sintering and pulverizing and depolymerization, lithium manganate positive electrode material with low internal resistance, long cycle stability and high capacity was prepared.

Benefits of technology

It improves the cycle stability and capacity of lithium manganese oxide positive electrode material, reduces the difficulty and cost of preparation process, is suitable for industrial production, and improves the cycle performance of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119176582A_ABST
    Figure CN119176582A_ABST
Patent Text Reader

Abstract

The invention provides a lithium manganate positive electrode material and a preparation method and application thereof, and belongs to the technical field of lithium ion battery materials. The lithium manganate positive electrode material with low internal resistance, long circulation and high capacity is obtained by mixing and sintering a lithium source, a manganese source and an additive in a mixed manner by adopting dry-process mixing and segmented reverse-sequence sintering and then performing depolymerization treatment. The lithium manganate positive electrode material prepared by the invention has the characteristics of relatively narrow particle size distribution, relatively small BET (Brunauer, Emmett and Teller) and high tap density and volume energy density; the lithium ion battery assembled by the positive electrode material has excellent first effect and capacity retention ratio under a high-temperature test condition, and the cycle performance of the lithium ion battery is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion battery materials, and in particular to a lithium manganate positive electrode material and a preparation method and application thereof. Background Art

[0002] Lithium manganese oxide has great advantages in the lithium-ion power supply market due to its low cost, environmental friendliness and abundant manganese resources. However, the reversible capacity decay of lithium manganese oxide positive electrode materials during charging and discharging at high temperatures has restricted its commercial development. Although the mechanism of its capacity failure is not fully understood, it is generally believed that its capacity failure is caused by the following three reasons:

[0003] 1) Jahn-Teller effect: This effect causes Mn 3+ The lattice structure is distorted, causing an irreversible transformation from cubic to tetragonal, resulting in lattice collapse and ultimately rapid attenuation of reversible capacity. 2) Manganese dissolution: Mn 3+ Disproportionation reaction of 2Mn 3+ (s)→Mn 4+ (s)+Mn 2+ (1) At the same time, the decomposition of lithium salts such as LiPF6 in the electrolyte produces HF, which accelerates the dissolution of manganese, resulting in the loss of active substances, and finally leads to a decrease in discharge capacity and cycle performance; 3) Oxidative decomposition of the electrolyte. Under high voltage, the oxidative decomposition of the electrolyte will cause the formation of an inert material SEI film on the surface of the positive electrode material, which will cover the surface of the material and hinder the Li + Diffusion increases the internal resistance and reduces the reversible capacity.

[0004] Chinese patent CN114933333A discloses a method for preparing a composite doped modified capacity type lithium manganese oxide material, which is mixed with manganese dioxide, lithium carbonate, niobium pentoxide, aluminum fluoride and aluminum hydroxide by dry ball milling; the lithium manganese oxide material is sintered at a sintering temperature of 735-745°C and a sintering time of 15h. The lithium manganese oxide obtained in this patent has a low initial capacity and initial efficiency, and the sintering time of the sample is relatively long.

[0005] Chinese patent CN117766713A discloses a preparation method of lithium niobate coated spinel modified lithium manganate material. The patent uses lithium carbonate, manganese tetraoxide, aluminum oxide, zirconium oxide and ammonium fluoride as reaction raw materials to synthesize multi-element doped lithium manganate material by a one-step solid phase method, and then wet-coats lithium niobate to obtain higher reversible capacity and better cycle performance. However, the patent uses manganese tetraoxide as a manganese source, and its vibration and compaction density is low. It is easy to harden after sintering, and it sticks in the sagger, making it difficult to remove the sagger; and the use of ammonium fluoride as a fluorine source does not meet the current environmental protection requirements, nor is it conducive to large-scale industrial production, and increases the difficulty and cost of tail gas treatment. The use of a wet secondary coating process will increase the material drying link, which will invisibly increase the manufacturing cost. The patent uses two sinterings, which invisibly increases the process difficulty and manufacturing cost of the sintering link.

[0006] Patent CN103236538A discloses a method for preparing lithium manganate by inflection point control. The patent mixes manganese dioxide, lithium carbonate and additives, heats the raw materials to 450-550°C, and keeps them warm for 2-4 hours to obtain a pre-burned material. Inflection point control: Heat the pre-burned material to 910-930°C in the air, keep it warm for 1-2 hours, then cool the pre-burned material after inflection point control to 820-850°C, keep it warm for 4-8 hours, and cool it. The inflection point control method of this patent has high requirements for the length of the sintering kiln of lithium manganate (effective length>60m, so this method is generally called positive sequence jump sintering method), and a long cooling period is required after the inflection point jump to meet the method. Therefore, the implementation of this method is difficult and the equipment investment is large.

[0007] In summary, the current preparation of lithium manganate uses manganese dioxide or manganese tetraoxide as raw materials. Although the lithium manganate prepared with manganese dioxide as the manganese source has high vibration and compaction density, the manganese dioxide material contains a large amount of impurities, resulting in low capacity of the lithium manganate product and poor cycle performance. The lithium manganate prepared using manganese tetraoxide as the manganese source has a high purity, high capacity and good cycle performance, but its vibration and compaction density is reduced, and it is easy to compact after sintering, and adhesion in the sagger will cause difficulty in removing the sagger. Summary of the invention

[0008] The object of the present invention is to provide a lithium manganese oxide positive electrode material and a preparation method and application thereof, wherein the lithium manganese oxide positive electrode material has low internal resistance, long cycle stability and high capacity characteristics.

[0009] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0010] The present invention provides a method for preparing a lithium manganate positive electrode material, comprising the following steps:

[0011] A manganese source, a first lithium source and an additive are mixed by a first dry ball milling process to obtain a first lithium manganate precursor; the additive comprises at least two of niobium pentoxide, niobium hydroxide, aluminum oxide, aluminum hydroxide, pseudo-boehmite, boehmite, lithium fluoride, aluminum fluoride, ammonium fluoride and hydrofluoric acid, and the additive comprises elements Al, F and Nb at the same time;

[0012] Performing a second dry ball milling on the first lithium manganese oxide precursor and the second lithium source to obtain a second lithium manganese oxide precursor;

[0013] The second lithium manganate precursor is sequentially subjected to reverse sintering in sections and crushing and depolymerization to obtain a lithium manganate positive electrode material.

[0014] Preferably, the first lithium source includes at least one or more of lithium carbonate, lithium hydroxide, lithium fluoride, lithium oxalate and lithium sulfate; the manganese source includes one or more of manganese tetraoxide, electrolytic manganese dioxide, manganese carbonate, manganese acetate and manganese sulfate.

[0015] Preferably, the molar ratio of Mn element to Li element in the manganese source and the first lithium source is 2:(1.06-1.20).

[0016] Preferably, the mass of the additive is 0.1-10% of the total mass of the manganese source and the first lithium source.

[0017] Preferably, the grinding equipment used for the first dry ball milling and the second dry ball milling are independently planetary ball mills or oblique ball mills, and the conditions for the first dry ball milling and the second dry ball milling independently include: a ball milling speed of 200 to 400 rpm, a ball milling time of 2 to 3 hours, a ball-to-material ratio of 1:1 to 4, and a particle size range of the first lithium manganese oxide precursor of 10 to 15 μm; the particle size range of the second lithium manganese oxide precursor is 6 to 10 μm.

[0018] Preferably, the second lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium fluoride, lithium oxalate and lithium sulfate; the mass of the second lithium source is 0.1-10% of the mass of the first lithium manganate precursor.

[0019] Preferably, the atmosphere of the staged reverse sintering is air, the temperature is 650-850°C, and the total sintering time is 10-26h; the staged reverse sintering includes a first stage of jump sintering, a second stage of cooling sintering and annealing performed in sequence; the temperature of the first stage of jump sintering is 750-820°C, and the holding time is 1-5h; the temperature of the second stage of cooling sintering is 650-750°C, and the holding time is 1-12h; the temperature of the annealing is 600-800°C, and the holding time is 4-10h.

[0020] Preferably, the pulverizing and deagglomerating process takes 1 to 60 minutes and the rotation speed is 100 to 10,000 r / min.

[0021] The present invention provides a lithium manganate positive electrode material prepared by the preparation method described in the above technical solution.

[0022] The present invention provides the application of the lithium manganate positive electrode material described in the above technical solution in a lithium ion battery.

[0023] The present invention provides a method for preparing a lithium manganese oxide positive electrode material, which adopts dry mixing and segmented reverse sintering, mixes a lithium source, a manganese source and an additive, and performs dry ball milling to obtain a first precursor, and then adds a lithium source through secondary ball milling to contact the additive Al in the first ball milled precursor to produce a lithium aluminate coating, thereby reducing manganese dissolution loss and improving the cycle life of the material, thereby improving the cycle stability and capacity of the lithium manganese oxide positive electrode material. At the same time, the present invention uses Al and F co-doping to allow part of the Al element to enter the internal structure of the lithium manganese oxide to replace part of the manganese atoms, making the spinel structure of the lithium manganese oxide more stable, and improving the electrochemical performance of the spinel lithium manganese oxide; wherein the F element enters the internal lattice of the lithium manganese oxide, replacing part of the O 2- The number of negative charges in the crystal increases with the 2- The decrease in Mn leads to a lower average valence of manganese ions in the lattice, that is, Mn 3+ The AlF3 coating produced at the same time can block the corrosion of HF in the electrolyte and improve the cycle life of the material.

[0024] In addition, the doping of Nb element can reduce the average valence of manganese ions and increase the Mn 3+ Thus, the discharge specific capacity is improved, which makes up for the problem of low capacity when using electrolytic manganese dioxide to prepare lithium manganate; at the same time, the sintering temperature of the lithium manganate material can be reduced, thereby reducing the manufacturing cost. In addition, the present invention adopts depolymerization treatment to achieve low internal resistance, thereby obtaining a lithium manganate positive electrode material with low internal resistance, long cycle and high capacity.

[0025] The present invention adopts segmented reverse sintering, and can obtain a lithium manganese oxide positive electrode material with excellent cycle stability under the condition of shortening the calcination time, reducing the sintering time and reducing the difficulty of the sintering process, so that the lithium manganese oxide positive electrode material obtained by depolymerization treatment has the characteristics of narrow particle size distribution, small BET, high tap density and volume energy density; the lithium ion battery assembled from the positive electrode material has excellent first efficiency and capacity retention rate, and effectively improves the cycle performance of the lithium ion battery.

[0026] The preparation method of the invention is simple and feasible, the process is easy to control, the raw materials are cheap and easily available, it is safe and environmentally friendly, has low energy consumption, high efficiency, low manufacturing cost, and is suitable for industrial production.

[0027] Furthermore, the present invention uses electrolytic manganese dioxide as a manganese source to prepare lithium manganate material. After high-temperature sintering, the material has a loose texture and a high tap density. Through depolymerization treatment, a lithium manganate material with low internal resistance is obtained, which greatly saves the initial production capital investment. In addition, the present invention uses a low-temperature annealing process to adjust the content of lattice oxygen in lithium manganate, reduce the degree of disordered rearrangement of oxygen ions in the material, improve the electron transmission capacity of the lithium manganate material, reduce the internal resistance, and increase the specific capacity of lithium manganate. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a 1000x SEM image of the lithium manganate material obtained in Example 1;

[0029] Figure 2 This is a 5000x SEM image of the lithium manganate material obtained in Example 1;

[0030] Figure 3 This is a 10000x SEM image of the lithium manganate material obtained in Example 1;

[0031] Figure 4 The XRD diffraction pattern of the lithium manganate material prepared in Example 1;

[0032] Figure 5 This is the EDS partition diagram of the lithium manganate material obtained in Example 1;

[0033] Figure 6 This is the EDS spectrum of the lithium manganate material obtained in Example 1;

[0034] Figure 7 The charge and discharge curve of the lithium manganate material prepared in Example 1;

[0035] Figure 8 The cyclic stability diagram of the lithium manganate material prepared in Example 1 and the comparative samples BN-M04 and NM-14H;

[0036] Fig. 9 The capacity retention rate diagram of the lithium manganate material prepared in Example 1 and the comparative samples BN-M04 and NM-14H;

[0037] Fig.10 The cyclic stability diagram of the lithium manganate materials prepared in Example 1 and Comparative Example 8 and the comparative samples BN-M04 and NM-14H at 45°C in a high and low temperature test cabinet;

[0038] Fig.11 This is a graph showing the capacity retention rate of the lithium manganese oxide materials prepared in Example 1 and Comparative Example 8 and comparative samples BN-M04 and NM-14H at 45°C. DETAILED DESCRIPTION

[0039] The present invention provides a method for preparing a lithium manganate positive electrode material, comprising the following steps:

[0040] A manganese source, a first lithium source and an additive are mixed by a first dry ball milling process to obtain a first lithium manganate precursor; the additive comprises at least two of niobium pentoxide, niobium hydroxide, aluminum oxide, aluminum hydroxide, pseudo-boehmite, boehmite, lithium fluoride, aluminum fluoride, ammonium fluoride and hydrofluoric acid, and the additive comprises elements Al, F and Nb at the same time;

[0041] Performing a second dry ball milling on the first lithium manganese oxide precursor and the second lithium source to obtain a second lithium manganese oxide precursor;

[0042] The second lithium manganate precursor is sequentially subjected to reverse sintering in sections and crushing and depolymerization to obtain a lithium manganate positive electrode material.

[0043] In the present invention, unless otherwise specified, the required raw materials for preparation are all commercially available products well known to those skilled in the art.

[0044] The present invention performs a first dry ball milling to mix a manganese source, a first lithium source and an additive to obtain a first lithium manganate precursor.

[0045] In the present invention, the first lithium source preferably includes at least one or more of lithium carbonate, lithium hydroxide, lithium fluoride, lithium oxalate and lithium sulfate; the manganese source preferably includes one or more of manganese tetraoxide, electrolytic manganese dioxide, manganese carbonate, manganese acetate and manganese sulfate; the particle size D of the electrolytic manganese dioxide is preferably 50 =5-20 μm. When the first lithium source or manganese source is two or more of the above, the present invention has no special limitation on the ratio of different types of lithium sources or manganese sources, and any ratio is acceptable.

[0046] In the present invention, the molar ratio of Mn element to Li element in the manganese source and the first lithium source is preferably 2:(1.06-1.20), and more preferably 2:(1.08-1.10).

[0047] In the present invention, the additive comprises at least two of niobium pentoxide, niobium hydroxide, aluminum oxide, aluminum hydroxide, pseudo-boehmite, boehmite, lithium fluoride, aluminum fluoride, ammonium fluoride and hydrofluoric acid, and the additive comprises elements Al, F and Nb at the same time, more preferably niobium pentoxide, aluminum fluoride and aluminum hydroxide; when the additive is two or more of the above, the present invention has no special limitation on the ratio of different types of additives, and any ratio is acceptable.

[0048] In the present invention, the mass of the additive is preferably 0.1 to 10% of the total mass of the manganese source and the first lithium source, more preferably 0.6 to 9.6%, and further preferably 3 to 5%.

[0049] In the present invention, the manganese source, the first lithium source and the additive are preferably mixed, and then the obtained mixed powder is subjected to a first dry ball milling mixing.

[0050] In the present invention, the grinding equipment used for the first dry ball milling is preferably a planetary ball mill or an oblique ball mill, and the conditions for the first dry ball milling preferably include: a ball milling speed of 200 to 400 rpm, more preferably 300 rpm, a ball milling time of 2 to 3 hours, a ball-to-material ratio of 1:1 to 4, and the particle size range of the first lithium manganese oxide precursor is preferably 10 to 15 μm, more preferably 10 to 13 μm.

[0051] After obtaining the first lithium manganate precursor, the present invention performs a second dry ball milling on the first lithium manganate precursor and a second lithium source to obtain a second lithium manganate precursor.

[0052] In the present invention, the second lithium source preferably includes one or more of lithium carbonate, lithium hydroxide, lithium fluoride, lithium oxalate and lithium sulfate; when the second lithium source is two or more of the above, the present invention has no special limitation on the ratio of different types of lithium sources, and any ratio is acceptable; the mass of the second lithium source is preferably 0.1-10% of the mass of the first lithium manganate precursor, more preferably 2-8%, and further preferably 3-5%.

[0053] In the present invention, the grinding equipment used for the second dry ball milling mixing is preferably a planetary ball mill or an oblique ball mill, and the conditions for the second dry ball milling mixing preferably include: a ball milling speed of 200 to 400 rpm, a ball milling time of 2 to 3 hours, a ball-to-material ratio of 1:1 to 4, and the particle size range of the second lithium manganese oxide precursor is preferably 6 to 10 μm.

[0054] After obtaining the second lithium manganate precursor, the present invention sequentially performs reverse sintering and crushing and depolymerization of the second lithium manganate precursor in sections to obtain a lithium manganate positive electrode material.

[0055] In the present invention, the atmosphere of the staged reverse sintering is preferably air, the temperature is preferably 650-850°C, and the total sintering time is preferably 10-26h; the staged reverse sintering preferably includes a first stage jump sintering, a second stage cooling sintering and annealing performed in sequence; the temperature of the first stage jump sintering is preferably 750-820°C, the holding time is preferably 1-5h, and the heating rate to the first stage jump sintering temperature is preferably 5°C / min; the temperature of the second stage cooling sintering is preferably 650-750°C, the holding time is preferably 1-12h, and the cooling rate to the second stage cooling sintering temperature is preferably 5°C / min; the annealing temperature is preferably 600-800°C, more preferably 700°C, and the holding time is preferably 4-10h; the cooling rate to the annealing temperature is preferably 3°C / min.

[0056] After completing the segmented reverse sintering, the present invention preferably cools to room temperature to obtain primary lithium manganate powder.

[0057] In the present invention, the pulverizing and deagglomerating time is preferably 1 to 60 min, more preferably 20 to 40 min, and the rotation speed is preferably 100 to 10000 r / min, more preferably 2000 r / min.

[0058] The present invention preferably uses a deagglomerator for crushing and deagglomeration to reduce the internal resistance of the powder, increase the tap density of the powder, and reduce the capacity loss of lithium manganese oxide due to excessive internal resistance during high-temperature long-distance transportation; more preferably, a deagglomerator is used, and the volume of the deagglomerator is preferably 1000L.

[0059] After the pulverization and depolymerization is completed, the present invention preferably sieves the obtained product through a 200-mesh sieve to obtain a lithium manganate positive electrode material.

[0060] The present invention provides a lithium manganate positive electrode material prepared by the preparation method described in the above technical solution.

[0061] The present invention provides the application of the lithium manganese oxide positive electrode material described in the above technical solution in a lithium ion battery. The present invention has no special limitation on the application method, and the application can be carried out according to methods well known in the art.

[0062] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0063] All raw materials are commercially available. Comparative sample NM-14H is a lithium manganate sample from Southern Manganese Industry Company, and BN-M04 is a lithium manganate sample from Henan Sodium Lithium Excellent Materials Technology Co., Ltd.

[0064] Example 1

[0065] S1: According to the molar ratio of Li / Mn = 1.08 / 2, weigh 1020g of electrolytic manganese dioxide (particle size D 50 =5-20 μm), 275 g lithium carbonate, additives (7.77 g niobium pentoxide, 38.85 g aluminum fluoride and 25.90 g aluminum hydroxide) were uniformly mixed in an oblique ball mill (the amount of each additive in the mixed powder was the percentage of the sum of the mass of electrolytic manganese dioxide and lithium carbonate: 0.6 wt% niobium pentoxide, 3 wt% aluminum fluoride, and 2 wt% aluminum hydroxide) to obtain a mixed powder;

[0066] S2: dry-milling the mixed powder obtained in S1 in an oblique ball mill at a ball mill speed of 300 r / min, a ball milling time of 2 h, and a ball-to-material ratio of 1:1 to obtain a first lithium manganese oxide precursor with a ball milling particle size of 10 to 13 μm;

[0067] S3: Add lithium carbonate (27.35 g) with a mass of 2% of the total mass of the first lithium manganate precursor in S1 to an oblique ball mill and mix, and continue ball milling at a ball mill speed of 300 r / min, a ball milling time of 2 h, and a ball-to-material ratio of 1:1 to obtain a second lithium manganate precursor with a ball milling particle size of 8 to 10 μm;

[0068] S4: The second lithium manganate precursor is subjected to segmented reverse sintering, wherein the temperature is raised to 800°C for the first sintering at a heating rate of 5°C / min, and the holding time is 2h; then the temperature is lowered to 750°C for the second sintering at a heating rate of 5°C / min, and the holding time is 12h; the temperature is lowered to 700°C for annealing at a cooling rate of 3°C / min, and the holding time is 4h, and then cooled to room temperature to obtain a primary lithium manganate powder;

[0069] S5: The sintered primary powder is depolymerized in a depolymerizer with a volume of 1000 L. The depolymerization time is 40 min and the rotation speed is 2000 r / min. The depolymerized powder is sieved through a 200-mesh sieve to obtain a lithium manganese oxide positive electrode material.

[0070] Example 2

[0071] The difference from Example 1 is that the additive in S1 is only niobium pentoxide (Nb2O5=7.77g), the amount of each additive in the mixed powder accounts for the percentage of the sum of the mass of electrolytic manganese dioxide and lithium carbonate: the mass percentage of niobium pentoxide is 0.6wt%, and the rest is the same as Example 1.

[0072] Example 3

[0073] The difference from Example 1 is that the additives in S1 are aluminum hydroxide (25.90 g) and aluminum fluoride (38.85 g), and the amount of each additive in the mixed powder accounts for the percentage of the sum of the mass of electrolytic manganese dioxide and lithium carbonate: the mass percentage of aluminum fluoride is 3wt%, and the mass percentage of aluminum hydroxide is 2wt%; the rest is the same as Example 1.

[0074] Example 4

[0075] The difference from Example 1 is that the additives in S1 are: niobium pentoxide = 12.95g, aluminum fluoride = 38.85g and aluminum hydroxide = 25.90g; the amount of each additive in the mixed powder is the percentage of the sum of the mass of electrolytic manganese dioxide and lithium carbonate: the mass percentage of niobium pentoxide is 1wt%, the mass percentage of aluminum fluoride is 3wt%, and the mass percentage of aluminum hydroxide is 2wt%; the rest is the same as Example 1.

[0076] Example 5

[0077] The difference from Example 1 is that the additives in S1 are: niobium pentoxide = 5.18g, aluminum fluoride = 38.85g and aluminum hydroxide = 25.90g; the amount of each additive in the mixed powder is the percentage of the sum of the mass of electrolytic manganese dioxide and lithium carbonate: the mass percentage of niobium pentoxide is 0.4wt%, the mass percentage of aluminum fluoride is 3wt%, and the mass percentage of aluminum hydroxide is 2wt%; the rest is the same as Example 1.

[0078] Example 6

[0079] The difference from Example 1 is that the additives in S1 are: niobium pentoxide = 7.77g, aluminum fluoride = 12.95g and aluminum hydroxide = 25.90g; the amount of each additive in the mixed powder accounts for the percentage of the sum of the mass of electrolytic manganese dioxide and lithium carbonate: the mass percentage of niobium pentoxide is 0.6wt%, the mass percentage of aluminum fluoride is 1wt%, and the mass percentage of aluminum hydroxide is 2wt%; the rest is the same as Example 1.

[0080] Example 7

[0081] The difference from Example 1 is that the additives in S1 are: niobium pentoxide = 7.77g, aluminum fluoride = 77.7g and aluminum hydroxide = 25.90g; the amount of each additive in the mixed powder accounts for the percentage of the sum of the mass of electrolytic manganese dioxide and lithium carbonate: the mass percentage of niobium pentoxide is 0.6wt%; the mass percentage of aluminum fluoride is 6wt% and the mass percentage of aluminum hydroxide is 2wt%; the rest is the same as Example 1.

[0082] Example 8

[0083] The difference from Example 1 is that the additives in S1 are: niobium pentoxide = 7.77g, aluminum fluoride = 38.85g and aluminum hydroxide = 12.95g; the amount of each additive in the mixed powder accounts for the percentage of the sum of the mass of electrolytic manganese dioxide and lithium carbonate: the mass percentage of niobium pentoxide is 0.6wt%, the mass percentage of aluminum fluoride is 3wt%, and the mass percentage of aluminum hydroxide is 1wt%; the rest is the same as Example 1.

[0084] Example 9

[0085] The difference from Example 1 is that the additives in S1 are: niobium pentoxide = 7.77g, aluminum fluoride = 38.85g and aluminum hydroxide = 77.7g; the amount of each additive in the mixed powder is the percentage of the sum of the mass of electrolytic manganese dioxide and lithium carbonate: the mass percentage of niobium pentoxide is 0.6wt%, the mass percentage of aluminum fluoride is 3wt%, and the mass percentage of aluminum hydroxide is 6wt%; the rest is the same as Example 1.

[0086] Example 10

[0087] The difference from Example 1 is that in S1, trimanganese tetraoxide is used as the Mn source, and the mass of trimanganese tetraoxide is 963 g; the rest is the same as Example 1.

[0088] Embodiment 11

[0089] The difference from Example 1 is that in S1, 1020 g of electrolytic manganese dioxide, 270 g of lithium carbonate and additives are weighed and uniformly mixed in an oblique ball mill according to a molar ratio of Li / Mn=1.06 / 2; the rest is the same as Example 1.

[0090] Example 12

[0091] The difference from Example 1 is that in S1, 1020 g of electrolytic manganese dioxide, 280 g of lithium carbonate and additives are weighed and uniformly mixed in an oblique ball mill according to the molar ratio of Li / Mn=1.10 / 2; the rest is the same as Example 1.

[0092] Embodiment 13

[0093] The difference from Example 1 is that: in S5, the sintered product is subjected to depolymerization treatment; the depolymerization and disintegration machine has a volume of 1000L, a depolymerization time of 20min, and a rotation speed of 2000r / min; the rest is the same as Example 1.

[0094] Embodiment 14

[0095] The difference from Example 1 is that: in S5, the sintered product is subjected to depolymerization treatment; the depolymerization and disintegration machine has a volume of 1000L, a depolymerization time of 60min, and a rotation speed of 2000r / min; the rest is the same as Example 1.

[0096] Comparative Example 1

[0097] The difference from Example 1 is that: the sintering method in S4 is one-time sintering, the sintering temperature is 750°C, and the holding time is 18h; the annealing cooling rate is 3°C / min, the annealing temperature is 700°C, the holding time is 2h, and the depolymerization treatment is carried out after cooling to room temperature; the rest is the same as Example 1.

[0098] Comparative Example 2

[0099] The difference from Example 1 is that in S4, the second lithium manganate precursor is sintered in stages; wherein, the heating rate during the first stage sintering is 5°C / min, the calcination temperature is 750°C, and the holding time is 10h; the heating rate during the second stage sintering is 5°C / min, the calcination temperature is 800°C, and the holding time is 2h; there is no annealing sintering step; the rest is the same as Example 1.

[0100] Comparative Example 3

[0101] The difference from Example 1 is that the sintering method in S4 is a positive sequence single jump sintering, and single crystal lithium manganate is obtained after cooling and crushing; wherein, the heating rate during the first stage of sintering is 5°C / min, the roasting temperature is 750°C, and the holding time is 12h; the heating rate during the second stage of sintering is 5°C / min, the roasting temperature is 800°C, and the holding time is 2h; the annealing temperature is 700°C, the holding time is 2h, and the depolymerization treatment is carried out after cooling to room temperature; the rest is the same as Example 1.

[0102] Comparative Example 4

[0103] The difference from Example 1 is that the additive in S1 is only zirconium dioxide (ZrO2=64.75g), and the mass percentage of zirconium dioxide in the mixed powder is 5wt%; the rest is the same as Example 1.

[0104] Comparative Example 5

[0105] The difference from Example 1 is that the additive in S1 is only vanadium pentoxide (V2O5=64.75g), and the mass percentage of vanadium pentoxide in the mixed powder is 5wt%; the rest is the same as Example 1.

[0106] Comparative Example 6

[0107] The difference from Example 1 is that in S5, the sintered product is depolymerized; a dry ball mill is used for depolymerization, the volume of the machine is 250L, the depolymerization time is 30min, and the rotation speed is 20r / min. Others are the same as Example 1. The crushing and depolymerization effects of different powder depolymerization machines are investigated.

[0108] Comparative Example 7

[0109] The difference from Example 1 is that in S5, the sintered product is depolymerized and a VC mixer is used for depolymerization, the volume of the machine is 200L, the depolymerization time is 30min, and the rotation speed is 3000r / min. Others are the same as Example 1. The crushing and depolymerization effects of different powder depolymerization machines are investigated.

[0110] Comparative Example 8

[0111] The difference from Example 1 is that: in S5, no deagglomeration treatment is performed after sintering, and the powder is sieved through a 200-mesh sieve to obtain a spinel-type lithium manganese oxide positive electrode material; the rest is the same as Example 1.

[0112] Characterization and performance testing

[0113] 1) Figures 1 to 3 is a SEM image of the lithium manganate material obtained in Example 1; Figures 1 to 3It can be seen that the prepared lithium manganate grains are hard blocks composed of a large number of fine spherical particles, and the fine spherical particles are octahedral crystals; combined with the capacity retention rate of Example 1, it can be seen that Nb, Al, and F doping greatly reduce the dissolution loss caused by the Jahn-Teller effect of the sample and improve the service life of the material.

[0114] 2) Figure 4 is the XRD diffraction pattern of the lithium manganate material obtained in Example 1; Figure 4 It can be seen that the diffraction peaks of the example samples are consistent with the PDF card data, proving that Nb, Al, and F doping have no effect on the crystal structure of lithium manganese oxide.

[0115] 3) Figures 5-6 The EDS diagram of the lithium manganate material obtained in Example 1 is shown in FIG. Figures 5-6 It can be seen that Al, Nb and F elements are evenly and continuously distributed in the material.

[0116] 4) The lithium manganese oxide prepared in the embodiment and the comparative example was tested according to the indicators in Table 1. The results are shown in Table 2;

[0117] Among them, powder conductivity test: the conductivity of lithium manganese oxide is determined by using a four-probe powder conductivity tester: 0.5g of lithium manganese oxide sample is weighed and put into a mold, a pressure of 20MPa is applied, and the pressure is maintained for 5S to measure the conductivity.

[0118] Table 1 Performance parameters of lithium manganese oxide

[0119]

[0120] Table 2 Index data of lithium manganate obtained in Examples 1 to 14 and Comparative Examples 1 to 8

[0121]

[0122] 5) The charge and discharge performance test of the lithium manganate products prepared in all embodiments and comparative examples was carried out according to the following method:

[0123] The lithium manganate, acetylene black and PVDF prepared in different cases were mixed in a mass ratio of 8:1:1, and then ground into a uniform slurry after adding NMP and coated on aluminum foil. The mixture was placed in a vacuum drying oven at 120°C for 3 hours, and a CR2025 button battery was made with a metal lithium sheet as the negative electrode and 1M LiPF6 as the electrolyte. The electrochemical test voltage range was 3.0-4.3V, and 0.5C (1C = 110mAh / g) was cycled for 5 cycles and then 1C was cycled for 100 cycles (NMP: N-methyl-2-pyrrolidone; PVDF: polytetrafluoroethylene).

[0124] Table 3 Performance data of lithium manganate obtained from Examples 1 to 14 and Comparative Examples 1 to 8

[0125]

[0126]

[0127] From Table 2, Table 3 and Figure 7 The data shows that:

[0128] By comparing Example 1 with Examples 2-3 and Comparative Examples 4-5, by co-doping elements Al, Nb, F, Nb in the lithium manganate structure, 5+ It can effectively reduce the average valence of Mn in the material and increase the 3+ The amount of F can be reduced, thereby increasing the discharge capacity of lithium manganese oxide. Al can effectively improve the structural stability of the material. F elements can reduce the Mn content in lithium manganese oxide materials. 4+ The amount of Mn 3+ The amount of F can effectively improve the discharge capacity of the material. At the same time, F can combine with Al to further enhance the material's anti-dissolution performance, reduce the corrosion of HF decomposed in the electrolyte, and improve the cycle life of the material.

[0129] By comparing Example 1 with Example 10, lithium manganate is prepared using manganese tetraoxide as the Mn source. The tap density of the product is low, the sintered material is severely compacted and difficult to crush and screen, the first capacity is low, the first efficiency is good, and the cycle performance is good. However, the sample decays faster under high temperature conditions, but has no effect on the decay at room temperature.

[0130] By comparing Example 1 with Examples 11 to 12, different Li / Mn ratios in the materials result in different cycle stabilities of the samples after sintering. After sintering, the samples with lower Li content have poor material stability; the samples with higher Li content have higher pH after sintering, and the performance is not significantly improved, resulting in a waste of Li. Therefore, the Li / Mn ratio of the lithium manganate material is 1.08 / 2, which has the best effect.

[0131] By comparing Example 1 with Comparative Example 1, the sintering method is one-time sintering, the sintering temperature is 750° C., and the insulation time is 18 hours; the material sintered by this method has a longer reaction time, a larger specific surface area of ​​the sample, and a faster cycle attenuation.

[0132] By comparing Example 1 with Comparative Example 2, the sample without low-temperature annealing has a higher pH, and its first capacity and first efficiency are worse than those of Example 1, the capacity retention rate is significantly reduced, and the cycle attenuation is poor.

[0133] By comparing Example 1 with Comparative Example 3, the sintering method is positive sequence single jump sintering, and the first volume and first effect of the prepared samples are basically the same. However, the cooling time of the jump section of the sintered samples using this method is relatively long, and there are certain requirements on the length of the kiln in actual production, which limits the scope of application of this method.

[0134] By comparing Example 1 with Examples 4-5, the increase in the doping ratio of 1wt% of niobium pentoxide causes the pH of the material to decrease, and it is weakly acidic. Its first capacity and first efficiency are basically consistent with the doping ratio of 0.4wt% of niobium pentoxide, resulting in an increase in raw material costs. The pH of the doping of 0.4wt% niobium pentoxide increases significantly, and the cycle performance of the sample is poor. The doping ratio of 0.6wt% niobium pentoxide has the best effect.

[0135] By comparing Example 1 with Examples 6-7, the increase in the doping ratio of aluminum fluoride to 1wt% by mass causes the initial capacitance of the material to be low, the tap density to decrease, and the cycle of the sample to be relatively stable. When the doping ratio of aluminum fluoride is 6wt%, the initial capacitance and initial efficiency of the sample have basically no significant changes, but the cycle decay of the sample is relatively fast.

[0136] By comparing Example 1 with Examples 8-9, the sample with a mass percentage of aluminum hydroxide of 1wt% has higher initial capacity and initial efficiency, but poor cycle stability and rapid capacity decay. The sample with a mass percentage of aluminum hydroxide of 6wt% has a lower capacity and better cycle stability.

[0137] By comparing Example 1 with Examples 13-14 and Comparative Example 8, the depolymerization effect of the sintered sample directly affects the high temperature stability of lithium manganese oxide. Through the test of the powder conductivity of the finished lithium manganese oxide, the sample with higher conductivity has better high temperature stability. The depolymerization time of the powder affects the conductivity, which is too low. The tap density of the powder that has not been depolymerized is low and the cycle stability is poor. The sample depolymerized for 20 minutes has an increased tap density and a low conductivity. The conductivity of the sample depolymerized for 60 minutes is basically close to that of the sample depolymerized for 30 minutes.

[0138] By comparing Example 1 with Comparative Examples 6-7, the effects of powders after depolymerization and sintering by different equipment are compared. The powder depolymerized by a ball mill has a higher specific surface area; the powder depolymerized by a VC mixer has a higher powder conductivity, and the internal resistance of lithium manganese oxide is close to that of Example 1. The lithium manganese oxide powders prepared in Comparative Examples 6-7 generally have the problems of reduced initial capacity and initial efficiency, and poor cycle stability of the samples.

[0139] The lithium manganate material prepared in Example 1 and the comparative samples BN-M04 and NM-14H were tested for cycle stability and capacity retention rate. The results are shown in Figures 8-9 ;Depend on Figure 8 , 9 It can be seen that compared with the comparative samples BN-M04 and NM-14H, the cycle stability and capacity retention rate of Example 1 are significantly better than those of the comparative samples BN-M04 and NM-14H.

[0140] The lithium manganate materials prepared in Example 1 and Comparative Example 8 and the comparative samples BN-M04 and NM-14H were tested for cycle stability and capacity retention at 45°C in a high and low temperature test cabinet. The results are shown in Figures 10-11 ;Depend on Figures 10-11 It can be seen that the high-temperature electrochemical performance of the lithium manganese oxide prepared in Example 1 is significantly improved by depolymerizing the prepared powder, which is beneficial to the long-distance transportation and storage of this type of battery.

[0141] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a lithium manganese oxide positive electrode material, characterized in that: The following steps are involved: A manganese source, a first lithium source and an additive are mixed by a first dry ball milling process to obtain a first lithium manganate precursor; the additive comprises at least two of niobium pentoxide, niobium hydroxide, aluminum oxide, aluminum hydroxide, pseudo-boehmite, boehmite, lithium fluoride, aluminum fluoride, ammonium fluoride and hydrofluoric acid, and the additive comprises elements Al, F and Nb at the same time; Performing a second dry ball milling on the first lithium manganese oxide precursor and the second lithium source to obtain a second lithium manganese oxide precursor; The second lithium manganate precursor is sequentially subjected to reverse sintering in sections and crushing and depolymerization to obtain a lithium manganate positive electrode material.

2. The preparation method according to claim 1, characterized in that: The first lithium source includes at least one or more of lithium carbonate, lithium hydroxide, lithium fluoride, lithium oxalate and lithium sulfate; the manganese source includes one or more of manganese tetraoxide, electrolytic manganese dioxide, manganese carbonate, manganese acetate and manganese sulfate.

3. The preparation method according to claim 2, characterized in that: The molar ratio of the Mn element to the Li element in the manganese source and the first lithium source is 2:(1.06-1.20).

4. The preparation method according to claim 1 or 3, characterized in that: The mass of the additive is 0.1-10% of the total mass of the manganese source and the first lithium source.

5. The preparation method according to claim 4, characterized in that: The grinding equipment used for the first dry ball milling and the second dry ball milling are independently planetary ball mills or oblique ball mills, and the conditions for the first dry ball milling and the second dry ball milling independently include: a ball milling speed of 200 to 400 rpm, a ball milling time of 2 to 3 hours, a ball-to-material ratio of 1:1 to 4, a particle size range of the first lithium manganese oxide precursor of 10 to 15 μm; and a particle size range of the second lithium manganese oxide precursor of 6 to 10 μm.

6. The preparation method according to claim 1, characterized in that: The second lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium fluoride, lithium oxalate and lithium sulfate; the mass of the second lithium source is 0.1-10% of the mass of the first lithium manganate precursor.

7. The preparation method according to claim 1 or 6, characterized in that: The atmosphere of the staged reverse sintering is air, the temperature is 650-850°C, and the total sintering time is 10-26 hours; the staged reverse sintering includes a first stage of jump sintering, a second stage of cooling sintering and annealing performed in sequence; the temperature of the first stage of jump sintering is 750-820°C, and the holding time is 1-5 hours; the temperature of the second stage of cooling sintering is 650-750°C, and the holding time is 1-12 hours; the temperature of the annealing is 600-800°C, and the holding time is 4-10 hours.

8. The preparation method according to claim 7, characterized in that: The pulverizing and deagglomerating time is 1 to 60 minutes, and the rotation speed is 100 to 10000 r / min.

9. The lithium manganate positive electrode material prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the lithium manganate positive electrode material according to claim 9 in lithium ion batteries.

Citation Information

Patent Citations

  • Method for preparing lithium manganate through inflection point control

    CN103236538A

  • A composite-doped modified capacity-type lithium manganese oxide and its preparation method

    CN114933333A

  • Lithium niobate coated spinel modified lithium manganate as well as preparation method and application thereof

    CN117766713A

Cited By

  • Positive electrode material and preparation method thereof, positive electrode plate, battery and electric device

    CN120824356A